Plasmon Hybridizations in Compound Nanorod–Nanohole Arrays - Shahab Razavi; Yiping Zhao (Nanomaterials, 2023)
This study shows that a hybridized plasmonic mode, represented by an additional transmission peak, in a compound structure consisting of a nanorod embedded in a nanohole can be effectively described as a quasi-dipole oscillator. When two nanorods are introduced into a nanohole, these two quasi-dipoles can couple and hybridize, giving rise to two additional transmission peaks in the enhanced optical transmission spectrum. The relative intensities of these peaks can be controlled by adjusting the incident polarization, while their separations can be tuned by modifying the length of the nanorods. The concept of quasi-dipoles in compound nanohole structures can be further extended to predict the coupling behavior of even more complex compound configurations, such as multiple nanorods within nanoholes, resulting in the generation of multiple hybridization states. Consequently, the shape and response of the transmission peaks can be precisely engineered. This strategy could be used to design nanohole-based metasurfaces for applications such as ultra-thin optical filters, waveplates, polarizers, etc.